Sesquiterpene Coumarins from Ferula sinkiangensis Act as Neuroinflammation Inhibitors - Xing, Yachao; Li, Ning; Zhou, Di; Chen, Gang; Jiao, Kun; Wang, Wenli; Si, Yingying; Hou, Yue (Planta Medica, 2017)
Neuroinflammation mediated by microglia cells plays a critical role in the development of Alzheimer′s disease. To identify novel natural neuroinflammation inhibitors, a bioactivity-guided phytochemical research was performed on the traditional Chinese medicine “Awei”, that exhibited a significant inhibitory effect on nitric oxide production in over-activated microglia cells. The research identified sixteen bioactive sesquiterpene coumarins (two new and fourteen known ones) in the effective extract of Ferula sinkiangensis. Further, the anti-neuroinflammatory activities in BV-2 microglial cells were evaluated by monitoring LPS-induced nitric oxide production. In conclusion, the major constituent, (3′S, 5′S, 8′R, 9′S, 10′R)-kellerin (1.5 %, w/w), should be responsible for the anti-neuroinflammatory effect exhibited by Awei. Furthermore, it might be a potential natural therapeutic agent for Alzheimer′s disease. The research indicated moreover, that its primary mechanism is the inhibition of mRNA expression of the inflammatory cytokines nitric oxide, tumor necrosis factor-α, cyclooxygenase-2, interleukin-6 and interleukin-1β.
Keywords: Awei; resin of Ferula sinkiangensis; Umbelliferae; sesquiterpene coumarins; neuro-inflammation; Alzheimerʼs disease